ALIH TEHNOLOGI KEGIATAN MANAJEMEN KONSTRUKSI MENUJU PERSIAPAN PEMBANGUNAN PLTN DI INDONESIA - Utomo Utomo (BATAN, 2011)
TRANSFER OF TECHNOLOGY CONSTRUCTION MANAGEMENT ACTIVITIES TOPREPARATION OF NPP DEVELOPMENT IN INDONESIA (An Experience Of Mul ti Propose Reactor 30 Devel opment at Serpong). Management and development of a nuclear installati on coul d not be separated from the role of Construction Management in the pl anning stages of the project start until the commissioni ng. On the construction of nuclear install tions MPR 30 Serpong, the rol e of human resource of Indonesia particularly Batan has recei ved a lot of knowl edge and experiences i n the development process, the ongoing process of transfer of technology from the foreign consultants (Bechtel -USA) to Batan has been conducted at theti me, and at l east we are abl e to absorb knowledge and prove i t hrough to completi on development incl udi ng commissioni ng activiti es. In the course of the time human resource chal lenges are requi red to have individual skil ls and expertise suffici ent to handle a mega project such as nuclear power plants. Constructi on Management is managi ng a maj or project stages from planning, construction, procurement, i nstall ation commissioni ng until handover to the owner. Based on the experience of the construction of the RSG-LP, it i s expected that human resources that meet to the standards requi red competencies for the preparation of NPP i n Indonesia are fulfill ed. PROSES ALIH TEHNOLOGI KEGIATAN MANAJEMEN KONSTRUKSI MENUJUPERSIAPAN PEMBANGUNAN PLTN DI INDONESIA (Pengalaman Pembangunan Reaktor Serba Guna Serpong).Pengelolaan pembangunan i nstalasi nukli r tidak lepas dari peran Manajemen Konstruksi dal am ahapan proyek mulai perencanaan sampai kommisioning. Pada pembangunan i nstal asi nuklir RSG-LP Serpong peran SDM Indonesi a khususnya Batan telah banyak menimba pengalaman dal am proses pembangunan, pada saat it u proses alih tehnologi sedang berlangsung dari pihak konsul tan asing ( Bechtel-USA ) kepada Batan, setidaknya kit a mampu menyerap ilmu dan membuktikannya sampai sel esai pembangunan termasuk kegi atan kommisioning. Dalam perjalanan waktu tantangan SDM dituntut untukmemiliki kemampuan indifidual dan keahl ian yang memadai dal am menangani suatu mega proyek seperti pembangki t tenaga nuklir. Manaj emen Konstruksi merupakan tahapanpengel ol aan suatu proyek besar dari perencanaan, konstruksi , pengadaan ,kommisioni ng hingga serah terima instalasi kepada pemilik. Berdasarkan pengalaman pembangunan RSGLP, di harapkan kebutuhan SDM yang memiliki persyaratan standar kopetensi dapat terpenuhi menyongsong persiapan pembangunan PLTN di Indonesia